2017
DOI: 10.1016/j.engfracmech.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

General cracked-hinge model for simulation of low-cycle damage in cemented beams on soil

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…From Figure 3 (a) it is observed that the proposed secant unloading scheme does not comply perfectly with experimental curves due to the secant unloading scheme selected. However, it was proposed in [23] to define a fixed negative intersecting point σ k u of -0.4f t on the ordinate, for which results are shown in Figure 3 (b). In this model the parameter σ k u is fitted and the response simplified, i.e.…”
Section: Functionality Of Fatigue Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…From Figure 3 (a) it is observed that the proposed secant unloading scheme does not comply perfectly with experimental curves due to the secant unloading scheme selected. However, it was proposed in [23] to define a fixed negative intersecting point σ k u of -0.4f t on the ordinate, for which results are shown in Figure 3 (b). In this model the parameter σ k u is fitted and the response simplified, i.e.…”
Section: Functionality Of Fatigue Modelmentioning
confidence: 99%
“…In the present study the hinge formulation proposed by Skar et al [23] is applied. This hinge consists of fibers of concrete material, shown in Figure 4.…”
Section: The Mechanics Of the Fiber-hinge Modelmentioning
confidence: 99%
See 3 more Smart Citations